Fertility Preservation among Cancer Patients in Saudi Arabia: Knowledge and Attitudes of Medical Students - Karim Hamda Farhat; Mostafa Ahmed Arafa; Danny Munther Rabah; Deana Khalid Awartani; Shahad Hussein Bajunaid; Seham Majid Abdulkader; Khaled Arab Awartani; Alanoud Abdullah Albekairi; Mohamed Abdullah Al-Atawi; Mashael Marzouq AlShebly (Dubai Medical Journal)
Introduction: Cancer education and informing people about cancer treatment and its sequel and their fertility can significantly lessen their health risk. Objective: The aim of the current study was to assess medical students’ knowledge, attitudes, and understanding toward fertility preservation (FP) for cancer patients. Methods: This cross-sectional study was conducted among medical students at two universities in Riyadh. A questionnaire was developed based on different surveys and was adapted to our culture. It was composed of two parts: sociodemographic data and questions assessing students’ knowledge and attitudes regarding FP. The second section discussed factors that could influence the utilization of FP services. It was composed of 5 questions, 4-point Likert scale (greatly, usually, rarely, never) scored from 1 for never to 4 for greatly. Results: Students, particularly females, were more knowledgeable about different FP methods, such as Gonadotrophin releasing hormones, sperm cryopreservation, and oocyte cryopreservation. They stated that cost, lack of information, and access to FP services are the most common factors hindering the utilization of services. They expressed a good attitude toward FP; however, nearly half of them mentioned that cancer treatment should be started first before FP. Conclusion: This study demonstrated the respectable awareness and attitude of FP among Saudi medical students. However, some gaps are present, indicating the need to improve education about FP in the medical curriculum.